Using the Multiplicative Competitive Interaction Model of Market Share for Petroleum Brands in South Africa. - Beard, David (My University, 2011)
This purpose of this research is to investigate the appropriateness and effectiveness of using the Multiplicative Competitive Interaction (MCI) model to simulate the market share of the competitors in the South African Petroleum industry, using Brand Equity measures as the inputs. By calculating the sensitivity of each Brand Equity measure, it is possible to provide data for marketing managers of the petroleum companies to enable them to make better decisions when allocating resources to future marketing campaigns. The South African Petroleum industry represents a unique market in which to carry out this study. There are a limited number of large companies competing (with vast financial resources on which to draw), huge barriers to entry, price control of fuels through government legislation, fuel considered as a grudge purchase, and there is a common perception that all fuels are the same, no matter where purchased. The MCI model used in this study has been formulated to simulate the market shares of multiple competitors, and overcomes the problems of modeling the market share of one company in isolation. Any action taken by a single company will affect not only their own market share but also that of their competitors in the industry. Therefore, market data was collected for all of the competitors and used as the basis for the model. ii Brand equity measures such as Product Performance, Brand Loyalty and Brand Awareness are used as the inputs for this model. These measures were extracted from the literature and selected based upon their relevance to the petroleum industry. The sensitivity of these measures was calculated by modeling the actual market shares of the companies in three geographical regions of South Africa: Cape Town, Durban and Johannesburg & Pretoria. The results achieved from the MCI model include an 83% fit between actual market share and modeled market share. The sensitivities of the Brand Equity measures are valid and clearly indicate the effect that each one has on market share. Various scenarios have been investigated to model the effects of Brand Equity measures changes on market share, with interesting results. It appears that the MCI model can be used to model the petroleum industry, and provides valid results. It should be possible to use this model in many other industries as well.
MBA - WBS